Social Media Marketing Influence Analysis Brand Image: Product Quality Perception and Trust in Consumer Buying Interest in Mie Sedap Cup Products - Muhammad Fatkhan Falakh (Co-Value Jurnal Ekonomi Koperasi dan kewirausahaan, 2024)
This research was conducted on Sedaap cup noodle products produced by PT. WingsFood. From the data above, it shows that there has been a decline in the Top Brand Index for Mie Sedaap Cup products, especially from 2019-2022 or the last 4 years. This indicates that consumer buying interest is inconsistent and tends to decline, so it is of course interesting to research what factors influence consumer buying interest in Mie Sedaap Cup products. This research aims to find out the influence of social media marketing, brand image, product quality and trust on consumer buying interest in purchasing Mie Sedap Cup products. The sample for this research was 115 respondents, using purposive sampling or judgmental sampling techniques, namely a method of taking samples using criteria. The criteria that can be used as samples in this research are consumers who have purchased Sedaap Cup noodle products, are at least 17 years old and live in the city of Semarang. The data analysis method used in this research is multiple linear regression. The research results found that social media marketing had a positive and significant effect on consumer buying interest, brand image had a positive and significant effect on consumer buying interest, product quality had a positive and significant effect on consumer buying interest and trust had a positive and significant effect on consumer buying interest.